Local Wisdoms Based-English Varieties: A Study on the Development of ICT-Based Learning Materials-Development Model - Dedi Aprianto (Universitas Hamzanwadi, 2020)
English with global phenomena in its function as a communication language, (Lingua Franca or ELF), has the consequent emergence of English varieties. The existence of this variety as a result of the diversity of speakers who have mother tongue (L1) differs geographically-demographically also. These varieties occur minimally in the aspects of the lexicon, grammar, and phonology. On the other hand, aspects of local wisdoms (indigenous wisdoms) have the potential to produce linguistic elements. This paper is oriented to the English variety model based on local wisdoms in the development of information technology-assisted learning materials for secondary schools (SMP). A number of potential components of local wisdoms, such as; (1) Customary Ceremonies, (2) Cultural Heritage, (3) Natural Tourisms, (4) Traditional Transportation, (5) Traditional Games, (6) Cultural Infrastructure, (7) Traditional Clothing, (8) Cultural Heritage, ( 9) Museums, (10) Cultural institutions, (11) Arts, (12) Cultural villages, (13) Arts and crafts, (14) Folklore, and (15) Children's puppets, particularly in Lombok island area becoming English learning materials for junior high schools. In the framework of implementing the 2013 curriculum effectively, this elaboration refers to regulations of Permendikbud on Curriculum 2013, Basic Competencies of Curriculum 2013, Review of Curriculum Policy in Language Subjects, Main Thoughts and Recommendations on English Curriculum 2013, and Analysis of Content Standard of English subject for junior high school and senior high school. This is also strengthened by involving relevant institutional elements and the association of teacher council through MGMP (Musyawarah Guru Mata Pelajaran). Then, materials related to information technology must involve experts in the field of Information Technology and Computer Science who have competence in so-called field. This is done by looking at the diversity of local wisdoms through translation from the first language (Indonesian/regional) to the target language (English). In the process of language translation, the theory that is referred to is the theory of Larson (1998), Meaning-Based Translation which is about the features and relations of semantic components as characteristics possessed by all languages, which consist of; Objects (Nouns and Pronouns, Events (Verbs), Attributes (Adjective and Adverb) and Relations (Conjunctions, Prepositions, Articles, Enclitics, etc.). While in relation with jargon and technical terms, this paper refers to Wuster (1979) theory views that the size of the translation of messages between two languages is based on the characteristics and concept of the message from the elements of meaning.